REFINING GEOIDAL HEIGHTS COMPUTED BY FULLY-NORMALISED SPHERICAL HARMONICS COEFFICIENTS OF THE EARTH GRAVITATIONAL MODEL EGM2008 BY ADJUSTMENT OF COMBINED GPS/LEVELLING/GEOID NETWORK - Luyen, Bui Khac (Vietnam Journal of Earth Sciences, 2014)
The paper presents the combined adjustment of GPS/Levelling bservations on benchmarks with gravimetric geoid heights of the Earth Gravitational Model EGM2008 on both terms of theoretical and practical point of view. For the parametric models to be used, various choice have been tested, namely well-known four- and five-parameter similarity transformation models and 1st, 2nd, 3rd order polynomial ones.The geoid heights of GPS/Levelling points in Vietnam territory were computed by the use of fully-normalised spherical harmonic coefficients of the Earth Gravitational Model (EGM) 2008 up to degree 2190.All five models have been tested employing GPS/Levelling observations, geoid heights from EGM2008 with a uniform accuracy for all height types. The mean deviation can be attributed to some datum bias and other systematic errors which was eliminated by the mathematical models after the fit. From the results which are summarized in the paper, it becomes evident that the best fit is achieved when the 3rd order polynomial model is employed to model the residuals. After the fit by 3rd polynomial model, a reduction by 54 cm and 1cm correspoding to RMS and standard deviation is achieved while the range reduces from 1.783m to 1.714m. References Christian Hirt, 2012. Efficient and accurate high-degree spherical harmonic synthesis of gravity field functionals at the Earth’s surface using the gradient approach. Journal of Geodesy,Volume 86, pp 729-744, Springer-Verlag. G. Fotopoulos, 2005. Calibration of geoid error models via a combined adjustment of ellipsoidal, orthometric and gravimetric geoid height data.Journal of Geodesy, Volume 79,pp 111-123, Springer-Verlag. C. Kotsakis, M. G. Sideris, 1999. On the adjustment of combined GPS/Levelling/geoid networks.Journal of Geodesy, Volume 73, pp 412- 421, Springer-Verlag. Nikolaos K. Pavlis, Simon A. Holmes, Steve C. Kenyon and John K. Factor, 2012. The development and evaluation of the Earth Gravitational Model 2008 (EGM2008). Journal of Geophysical Research, vol 117. Pavlis NK, Holmes SA, Kenyon SC, Factor JK, 2008. An Earth Gravitational Model to Degree 2160: EGM2008.Presented at the 2008 General Asembly of the European Geosciences Union, Vienna, Austria, April 13-18. N. Tziavos, G. S. Vergos, V. N. Grigoriadis, V. D. Andritsanos, 2012. Adjustment of collocated GPS, geoid and orthormetric height observations in Greece. Geoid or Orthometric height improvement?. International Association of Geodesy Symposia, Volume 136, pp 481-488, Springer Berlin Heidelberg.